Political institutions and economic growth in Africa's 'Renaissance'. (11th October 2017) - Bates, Robert H; Block, Steven
Abstract: In the late twentieth and early twenty-first centuries, many African states replaced authoritarian political regimes with competitive electoral systems; the economies of many also began to grow, some for the first time in decades. We argue that democratic reform led to economic growth, as did Acemoglu, Naidu, Restrepo and Robinson in an earlier paper. Our approach differs from theirs in that while we to seek to identify a causal relationship between democracy and development, we build our analysis around the qualitative accounts of regional specialists and the reasoning of political economists. Where others test for the existence of a causal account, we test for the existence of specific casual mechanisms.